The Relationship Between the Taghanic Unconformity and Marcellus Shale Production in Doddridge and Ritchie Counties, West Virginia - Adams, Emily (East Carolina University, 2016)
The Marcellus Shale, a geologic unit that extends from New York to West Virginia within the Appalachian region, is the source of trillions of cubic feet of natural gas due to organic-rich properties. The formation of the unit was coupled with a period of eustatic sea-level rise that resulted in reactivation of a peripheral bulge leading to the development of the Taghanic unconformity. Stratal variances such as thinning or removal of units within the region are predominately found within the Marcellus Shale as a result of the Taghanic unconformity. Most specifically, in West Virginia, the Taghanic unconformity dominates Marcellus Shale thickness deviations. Areas where thickness of the unit varies considerably are located within Doddridge and Ritchie counties. This project aids in understanding how stratigraphic thinning or removal of the Marcellus Shale in relation to hydrocarbon production differences between Doddridge and Ritchie counties, West Virginia may be a result of the Taghanic unconformity. Data are derived from log images obtained by the West Virginia Geological and Economic Survey that are correlated to establish the stratigraphy. This study shows the Middle Devonian Marcellus Shale thins from ~55-95 feet in the northeast to ~15-60 feet in the southwest of the counties. This is the result of depositional thinning of the lower Marcellus Shale and erosional removal of part of the upper Marcellus Shale. Additionally, the erosional boundary becomes more extensive towards the southwest. The average first 12 months of gas production from the Marcellus Shale indicates a larger quantity produced within Doddridge County (656,411 MCF) in comparison to Ritchie County (94,209 MCF). Variations in production values may be attributed to erosional features and thinning trends of the Marcellus Shale related to the Taghanic unconformity as well as additional factors such as gas extraction method, and reservoir properties.
Keywords: Marcellus Shale; Unconformities (Geology)--West Virginia; Sea level; Erosion; Natural gas--Geology